Community social capital and tooth loss in Japanese older people: a longitudinal cohort study. Issue 4 (5th April 2016) - Koyama, Shihoko; Aida, Jun; Saito, Masashige; Kondo, Naoki; Sato, Yukihiro; Matsuyama, Yusuke; Tani, Yukako; Sasaki, Yuri; Kondo, Katsunori; Ojima, Toshiyuki; Yamamoto, Tatsuo; Tsuboya, Toru; et al.
Abstract : Objective: To date, no study has prospectively examined the association between social capital (SC) in the community and oral health. The aim of this longitudinal cohort study was to examine the association between both community-level and individual-level SC and tooth loss in older Japanese people. Design: Prospective cohort study Setting: We utilised data from the Japan Gerontological Evaluation Study (JAGES) performed in 2010 and 2013 and conducted in 525 districts. Participants: The target population was restricted to non-institutionalised people aged 65 years or older. Participants included 51 280 people who responded to two surveys and who had teeth at baseline. Primary outcome measure: The primary outcome measure was loss of remaining teeth, measured by the downward change of any category of remaining teeth, between baseline and follow-up. Results: The mean age of the participants was 72.5 years (SD=5.4). During the study period, 8.2% (n=4180) lost one or more of their remaining teeth. Among three community-level SC variables obtained from factor analysis, an indicator of civic participation significantly reduced the risk of tooth loss (OR 0.93; 95% CI 0.88 to 0.99). The individual-level SC variables 'hobby activity participation' and 'sports group participation' were also associated with a reduced risk of tooth loss (OR 0.88; 95% CI 0.81 to 0.95 and OR 0.90; 95% CI 0.82 to 0.99, respectively). Conclusions: Living in a community with rich SC and individuals with good SC is associated with lower incidence of tooth loss among older Japanese people.